2001
DOI: 10.1146/annurev.immunol.19.1.375
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Synapse

Abstract: The adaptive immune response is initiated by the interaction of T cell antigen receptors with major histocompatibility complex molecule-peptide complexes in the nanometer scale gap between a T cell and an antigen-presenting cell, referred to as an immunological synapse. In this review we focus on the concept of immunological synapse formation as it relates to membrane structure, T cell polarity, signaling pathways, and the antigen-presenting cell. Membrane domains provide an organizational principle for compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
583
0
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 815 publications
(608 citation statements)
references
References 114 publications
14
583
0
11
Order By: Relevance
“…4). The mapping of the binding site on domain 1 of CD200R together with the complementary data for CD200 itself [13] shows that the CD200/ CD200R interaction also spans this distance providing evidence for areas of close contact between myeloid and other cells in addition to the 'classical' synapse described for T cell interactions [2,11]. Interactions between the membrane proteins of myeloid and cells other than lymphocytes are less well characterized than those of T cells and dendritic cells, but it is notable that the CD47/signal regulatory protein (SIRP) § interaction also spans four IgSF domains although in this case the SIRP § contains three domains and CD47 one domain [20].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…4). The mapping of the binding site on domain 1 of CD200R together with the complementary data for CD200 itself [13] shows that the CD200/ CD200R interaction also spans this distance providing evidence for areas of close contact between myeloid and other cells in addition to the 'classical' synapse described for T cell interactions [2,11]. Interactions between the membrane proteins of myeloid and cells other than lymphocytes are less well characterized than those of T cells and dendritic cells, but it is notable that the CD47/signal regulatory protein (SIRP) § interaction also spans four IgSF domains although in this case the SIRP § contains three domains and CD47 one domain [20].…”
Section: Discussionmentioning
confidence: 90%
“…In T cells these proteins often interact with other proteins with two IgSF domains in an end-to-end topology. For these interactions to occur, the opposing cell membranes need to come into close proximity and the size of the interacting proteins has been shown to be important in the formation of the immunological synapse and triggering of T cells [10][11][12]. Mutagenesis analysis of CD200 indicated that the N-terminal (membrane-distal) domain of CD200 contains the CD200R binding site [13].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was thought that these assemblies were large and involved extensive immunoreceptor clustering. For example, it has been suggested that the immunological synapse that forms between the T cell and the Ag-presenting cell facilitates T cell receptor signaling by clustering the receptor and other signaling molecules [20]. Recent studies indicated, however, that initiation of T cell receptor-mediated signaling could occur early and could largely precede the formation of the mature immunological synapse [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In control cells exposed to 125 I-IgE instead of anti-Fc 4 RI Ab, most of the 125 I-IgEFc 4 RI complexes (94±8%; mean ± SD, n=4) were found in the high-density fractions of the sucrose gradient (fractions [11][12][13][14][15][16][17][18][19][20][21][22], and only a small portion (5.8±2.2%) was found in the low-density fractions (fractions 1-10; Fig. 1E, F).…”
Section: Differences In Degranulation Calcium Response and Drm Recrumentioning
confidence: 99%
“…T cell-APC interactions have been studied dynamically in vitro and components of the molecular structures that comprise the synapse have been elegantly characterized [1,2,3]. More recently in vivo documentation of T cell and APC trafficking and interactions have been documented, especially through the use of two photon confocal microscopy [4,5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%